2007
DOI: 10.1016/j.mod.2007.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid-mediated patterning of the pre-pancreatic endoderm in Xenopus operates via direct and indirect mechanisms

Abstract: Early patterning of the endoderm as a prerequisite for pancreas specification involves retinoic acid (RA) as a critical signalling molecule in gastrula stage Xenopus embryos. In extension of our previous studies, we made systematic use of early embryonic endodermal and mesodermal explants. We find RA to be sufficient to induce pancreas-specific gene expression in dorsal but not ventral endoderm. The differential expression of retinoic acid receptors (RARs) in gastrula stage endoderm is important for the distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 49 publications
2
32
1
1
Order By: Relevance
“…In addition, zebrafish and Xenopus embryos treated with exogenous RA showed enlargement of the pancreas, as well as enlargement of the liver in zebrafish, in the anterior direction (Stafford and Prince, 2002;Chen et al, 2004;Stafford et al, 2004). A recent study reported that RA is sufficient to induce pancreas-specific gene expression in the dorsal but not the ventral endoderm (Pan et al, 2007). Mouse embryos deficient for the RA-synthesizing enzyme retinaldehyde dehydrogenase 2 (RALDH2), if rescued from early lethality by maternal RA, lack active RA signaling in the foregut region.…”
Section: In Vitro Pancreas-induction Systems Using Undifferentiated Xmentioning
confidence: 96%
“…In addition, zebrafish and Xenopus embryos treated with exogenous RA showed enlargement of the pancreas, as well as enlargement of the liver in zebrafish, in the anterior direction (Stafford and Prince, 2002;Chen et al, 2004;Stafford et al, 2004). A recent study reported that RA is sufficient to induce pancreas-specific gene expression in the dorsal but not the ventral endoderm (Pan et al, 2007). Mouse embryos deficient for the RA-synthesizing enzyme retinaldehyde dehydrogenase 2 (RALDH2), if rescued from early lethality by maternal RA, lack active RA signaling in the foregut region.…”
Section: In Vitro Pancreas-induction Systems Using Undifferentiated Xmentioning
confidence: 96%
“…In these organisms, RA from the overlying mesoderm posteriorizes the gut endoderm and promotes pancreasorgan allocation during gastrulation. Blocking RA signaling inhibits pancreas specification suggesting that RA is essential in this process Prince 2002, Kumar et al, 2003;Chen et al, 2004b;Stafford et al, 2004Stafford et al, , 2006Pan et al, 2007;Bayha et al, 2009). Based on the distribution of in vivo RA receptors (RAR) and results of cell-transplantation assays, it was concluded that RA acts directly on the endoderm for pancreas specification in zebrafish (Stafford et al, 2006).…”
Section: Figmentioning
confidence: 99%
“…In addition, localized endodermal expression of different rar paralogs further fine-tunes this RA signaling activity along the AP axis of the developing endoderm (Bertrand et al, 2007;Mollard et al, 2000). Finally, localized expression of rars in dorsal and ventral areas of the vertebrate endoderm may even create differential RA signaling activities along the dorsoventral (DV) body axis (Pan et al, 2007). To understand how and when these complex patterns of RA signaling activity evolved in the endoderm, it will be crucial to study in much greater detail the functions of RA in the endoderm of different invertebrate systems.…”
Section: Endoderm Patterning and Pharyngeal Developmentmentioning
confidence: 99%